Neuroendocrine Tumor of the Fallopian Tube and Serous Adenocarcinoma of the Ovary: Multicentric Primary Tumors - Nataliia HYRIAVENKO; Mykola LYNDIN; Vladyslav SIKORA; Ruslana CHYZHMA; Yulia LYNDINA; Kateryna SIKORA; Wireko Andrew AWUAH; Anatolii ROMANIUK (Federation of Turkish Pathology Societies, 2023)
Neuroendocrine tumors (NETs) comprise a large group of tumors that are most often localized in the gastrointestinal tract and lungs. They are rarely found in the organs of the female reproductive tract; such NETs are primarily localized in the ovaries. We present a case of multicentric primary low-grade NET of the fallopian tube and high-grade ovarian serous adenocarcinoma. In both tumor regions, the histotypes of neoplasms were determined by morphological and immunohistochemical investigations. The NET of the fallopian tube was diffusely positive for chromogranin A and CD56, but wild type for p53 and negative for CK7, CK20, and ER; Ki-67 expression was observed in 3% of the neoplastic cells. The ovarian serous adenocarcinoma was positive for CK7 and ER, mutant for p53, but negative for chromogranin A, CK20, and CD56; Ki-67 expression was observed in 45% of the tumor cells. These results support the possibility that NET can occur in the female reproductive tract and coexist with other malignant tumors.